Optimization of vehicle front shape for pedestrian protection - Li, Guibing (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
The design of a vehicle front has a significant influence on pedestrian injury risk in the event of a vehicle collision. Although significant progress has been made in understanding which features of vehicle design are crucial for minimizing pedestrian injuries, an optimal vehicle design has not been achieved. A particular challenge is that the range of real world accident scenarios is not considered in current assessments of vehicle pedestrian safety performance. Therefore this thesis sets out to develop and evaluate an efficient and reliable approach for the assessment and optimization of vehicle front shape to reduce overall pedestrian injury risk.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; PhD Trinity College Dublin, 2017